A journey from darkness to dawn: Metaphoric variation in depression recovery stories posted on Chinese Wechat subscription accounts - Lin Lin; Rui Zhou; Jia-jia Wang (Language and Health)
Despite volumes of research on depression-related conceptual metaphors and the therapeutic function of client-generated metaphors, seldom efforts have been made to unveil clients’ positive changes signified by metaphoric variation in the context of recovery. Based on depression recovery stories posted on Chinese Wechat subscription accounts, this study unpicks evolved metaphoric patterns indicative of positive changes regarding altered attitudes toward depression, social interaction and healthcare services during depressed patients’ recovery. It is found that these varying patterns can be mostly decoded based on correspondence and class inclusion metaphor types, developing from specific original source-target relations or original elements of the sources, while the rest of them can be realized by the introduction of new sources or targets for elaborating new experience and outcomes. They reflect depression survivors’ positive thinking patterns, self-empowerment and resilience, and convey their experience-licensed suggestions and encouragement to peers. Additionally, this study discusses how the Chinese socio-cultural values play a vital role in the understanding of depression-related metaphors and their variation, and provides implications for the application of metaphoric techniques in healthcare practice with socio-cultural sensitivity.